Systemic inflammatory markers in individuals with cerebral palsy. (January 2019) - Pingel, Jessica; Barber, Lee; Andersen, Ida Torp; Walden, Ferdinand Von; Wong, Christian; Døssing, Simon; Nielsen, Jens Bo
Individuals with cerebral palsy (CP) develop skeletal muscle contractures that impair muscle function. In turn, contractures affect the ability to ambulate and often promote a sedentary lifestyle. The aim of the present study was to investigate the systemic inflammatory markers transforming growth factor beta-1 (TGFβ1), C-reactive protein (CRP), and interleukin-6 (IL-6) in children and adults with CP. Blood samples of n = 34 participants (24 individuals with CP (n = 14 children with CP age 10.36 ± 1.1 and n = 10 adults with CP age 38.80 ± 3.6) and 10 healthy adults age 36.63 ± 3.8) were analyzed for circulating levels of TGFβ1, CRP, and IL-6 using Sandwich Enzyme linked immunosorbent assay (ELISA) analyses (R&D systems). TGFβ1 and CRP levels were significantly higher in children with CP compared to both adults with CP (TGFβ1: P < 0.0005 and P < 0.0002, respectively) and healthy adults (CRP: P < 0.0001 and P < 0.0001, respectively), while no differences were observed between the adults with CP and healthy adults in TGFβ1 ( P = 0.29) and CRP ( P = 0.59), respectively. Furthermore, IL-6 levels showed no significant differences between the groups. The present findings indicate that the level of systemic inflammation is increased in children with CP. We speculate that persisting inflammation in children with CP might influence the development of muscle contractures, resulting in reduced muscle mass and marked muscle weakness in adults with CP.